Answer

Verified

408.3k+ views

**Hint:**In this question, we have to find the value of a cubic polynomial at 6. Thus, we start solving this problem by letting a function which is equal to the subtraction of cubic polynomial at a variable and the variable. Then, we will find f(x), where x=0, 1, 2. After that, we know that a cubic equation can be expressed as $f(x)=a(x-1)(x-2)(x-3)$ . After that we will find P(4) and then P(6), to get the required result for the problem.

**Complete step by step solution:**

According to the question, we have to find the value of $P(6)$ of a cubic equation.

Let there be a function, such that it is equal to the subtraction of cubic polynomial at a variable and the variable, that is

$f(x)=P(x)-x$ --------- (1)

Thus, now we will find f(1), f(2), and f(3) from equation (1), we get

$\begin{align}

& f(1)=P(1)-1 \\

& f(1)=1-1 \\

& f(1)=0 \\

\end{align}$

Similarly,

$\begin{align}

& f(2)=P(2)-2 \\

& f(2)=2-2 \\

& f(2)=0 \\

\end{align}$ , and

$\begin{align}

& f(3)=P(3)-3 \\

& f(3)=3-3 \\

& f(3)=0 \\

\end{align}$

Thus, we get that $f(x)=0$ where x=1, 2, and 3.

Now, we will express the above equation in terms of a cubic polynomial as

$f(x)=a(x-1)(x-2)(x-3)$

$P(x)=a(x-1)(x-2)(x-3)+x$

Thus, $P(x)=f(x)+x$

$P(x)=a(x-1)(x-2)(x-3)+x$ -------- (2)

Now, we will put x = 4 and the value of P(4) from the question in equation (2), we get

$P(4)=a(4-1)(4-2)(4-3)+4$

On further simplification, we get

$5=a(3)(2)(1)+4$

On solving the brackets, we get

$5=6a+4$

Now, we will subtract 4 on both sides in the above equation, we get

$5-4=6a+4-4$

As we know, the same terms with opposite signs cancel out each other, thus we get

$1=6a$

So, we will divide 6 on both sides in the above equation, we get

$\dfrac{1}{6}=\dfrac{6}{6}a$

Thus, on further simplification, we get

$a=\dfrac{1}{6}$ ------------ (3)

Therefore, putting the value of equation (3) in equation (2), we get

$P(x)=\dfrac{1}{6}\left( (x-1)(x-2)(x-3) \right)+x$

Now, let x = 6 in the above equation, we get

$P(6)=\dfrac{1}{6}\left( (6-1)(6-2)(6-3) \right)+6$

On solving the brackets of the above equation, we get

$\begin{align}

& P(6)=\dfrac{1}{6}\left( (5)(4)(3) \right)+6 \\

& P(6)=\dfrac{1}{6}\left( 60 \right)+6 \\

\end{align}$

On further simplification, we get

\[\begin{align}

& P(6)=10+6 \\

& P(6)=16 \\

\end{align}\]

**Therefore, the value of P(6) for the cubic polynomial is equal to 16.**

**Note:**While solving this question, make all the calculations properly to avoid error and confusion. In this type of question, the accurate answer is based on the value of a, which we find out through P(4), so make all the steps properly.

Recently Updated Pages

How many sigma and pi bonds are present in HCequiv class 11 chemistry CBSE

Mark and label the given geoinformation on the outline class 11 social science CBSE

When people say No pun intended what does that mea class 8 english CBSE

Name the states which share their boundary with Indias class 9 social science CBSE

Give an account of the Northern Plains of India class 9 social science CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

Trending doubts

Difference Between Plant Cell and Animal Cell

Which are the Top 10 Largest Countries of the World?

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

How do you graph the function fx 4x class 9 maths CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths